1993
DOI: 10.1111/j.1471-4159.1993.tb03571.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Modulates Nicotinic Responses of Adrenal Chromaffin Cells

Abstract: 5-Hydroxytryptamine (5-HT) specifically and reversibly inhibits nicotine-induced currents and catecholamine release in bovine adrenal chromaffin cells in culture. Pharmacological analysis indicates that the inhibition is not mediated by known 5-HT receptor subtypes. The inhibition is noncompetitive over a range of nicotine concentrations between 1 and 100 microM. Preincubation with either 5-HT or substance P significantly protects the response from nicotine-induced desensitization. It is concluded that 5-HT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Furthermore, agonists and antagonists of different 5HT receptor subtypes affected the AcCho currents in the same manner, and none of them produced the oscillatory currents characteristic of the activation of 5HT receptors expressed in oocytes (20). Thus, our results show that not only 5HT but also other serotonergic agents act directly on nAcChoRs, much in the same way that 5HT affects the nAcChoRs in other cells (4,16,18).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Furthermore, agonists and antagonists of different 5HT receptor subtypes affected the AcCho currents in the same manner, and none of them produced the oscillatory currents characteristic of the activation of 5HT receptors expressed in oocytes (20). Thus, our results show that not only 5HT but also other serotonergic agents act directly on nAcChoRs, much in the same way that 5HT affects the nAcChoRs in other cells (4,16,18).…”
Section: Discussionsupporting
confidence: 61%
“…The IC50 for blockage of AcCho responses by 5HT was -100 ,uM in chick ciliary ganglion neurons (17), C2 myotubes (4), muscle receptors expressed in oocytes (ref. 4 and unpublished results), in bovine chromaffin adrenal cells (18), and in a2,34 neuronal nAcChoRs.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This would resemble the effects of hexamethonium, which appears to inhibit muscle AChRs competitively (Rang & Rylett, 1984) but neuronal receptors non-competitively (Charnet et al 1992). However, we have reported that in oocytes expressing the á2â4 neuronal AChR subtype the ACh-current is inhibited by 5_HT in a noncompetitive and voltage-dependent fashion (Garc úa-Colunga & Miledi, 1994, which is similar to the effects of 5_HT on chromaffin cells (Vijayaraghavan et al 1993) and on á7 homomeric AChR (Palma et al 1997).…”
Section: Effects Of Serotonergic Agents On Muscle Achrsmentioning
confidence: 81%
“…Similar mechanisms have been proposed for neuronal AChRs (Akasu & Koketsu, 1986). On the other hand, it has been suggested that 5_HT and other serotonergic agents non-competitively inhibit adult and embryonic muscle, Torpedo and neuronal AChRs, by blocking the ionic channel (Grassi et al 1993;Vijayaraghavan et al 1993;Garc úa-Colunga & Miledi, 1994Palma et al 1996Palma et al , 1997 Garc úa-Colunga et al 1997a,b).…”
Section: Discussionmentioning
confidence: 93%